Frontal Ostium Grade (FOG): A New Computer Tomography Grading System for Endoscopic Frontal Sinus Surgery. (September 2020) - Gheriani, Heitham; Al-Salman, Rami; Habib, Al-Rahim R.; Javer, Amin
Objective: The location and size of the frontal sinus ostium are critical in determining surgical difficulty. The more anterior the ostium, the more difficult is the surgical access. We propose a novel computed tomography (CT) grading specific to the anatomical position of the frontal ostium. Study Design: Observational study followed by a prospective part. Settings: Tertiary rhinology practice Subject and Methods: On a specified sagittal CT cut, a vertical line was drawn through the posterior edge of the frontal process of the maxilla (frontal buttress/beak) along its vertical axis (reference [R-] line). A second (S-) line was placed at the point of upturn of the skull base. Based on if the S-line was posterior or anterior to the R-line, the frontal ostium was graded positive and more easily accessible or negative and thereby more challenging, respectively. If both lines overlapped, then a neutral (0) grading existed. Results: A total of 297 CTs (594 ostia) were analyzed. In total, 394 (65%) ostia were grade positive, 52 (8.75%) were grade negative, and 103 (17.3%) were grade neutral. Ninety frontal sinusotomies were then performed using this grading system: 48 were positive, 21 negative, and 21 neutral. The average time to complete a frontal sinusotomy was 9.96 minutes for grade positive compared to 11.4 minutes for neutral and 16.05 minutes for grade negative ( P < .005). Conclusion: This novel anatomical CT grading system is designed to be useful in planning and predicting the level of difficulty in endoscopic frontal sinus surgery.